Exploring the Polarization Photocatalysis of ZnIn2S4 Material toward Hydrogen Evolution by Integrating Cascade Electric Fields with Hole Transfer Vehicle. (22nd June 2022) - Wan, Jun; Liu, Lin; Wu, Yan; Song, Jiarui; Liu, Jiaqing; Song, Ru; Low, Jingxiang; Chen, Xiaoli; Wang, Jijiang; Fu, Feng; Xiong, Yujie
Abstract: Sluggish charge kinetics in photocatalysts and slow hole transfer in oxidation half‐reaction severely limit the photocatalytic activity of hydrogen evolution. ZnIn2 S4 with an asymmetrical layered structure of [S–In]–[S–In–S]–[Zn–S] unit cell is a promising material offering asymmetrical crystal polarization to overcome the limitation; however, the polarization‐induced internal electric field by this material remains largely unexplored. Herein, the polarization‐induced internal electric field of ZnIn2 S4 by engineering the polarity intensity in microscopic units is demonstrated for the first time. Specifically, ultrathin ZnIn2 S4 nanosheets are employed to establish a Ni12 P5 /ZnIn2 S4 ‐O (NP/ZIS‐O) system with powerful bulk and interface cascade electric field by the oxygen doping and ohmic junction. Enabled by such a design, the photogenerated electrons can rapidly migrate to NP active sites, suppressing the photogenerated electron‐hole pair recombination on ZIS‐O. To further overcome the inefficient hole transfer in oxidation half‐reaction, the preferential dehydrogenation of the α‐CH bond in benzyl alcohol is utilized as a vehicle to facilitate hole transfer. As a result, a remarkably enhanced H2 generation of 15.79 mmol g –1 h –1 is achieved on NP/ZIS‐O, which is 8.16‐fold higher than that of pristine ZnIn2 S4 . Meanwhile, as a value‐added oxidation product, benzaldehyde can be produced at the rate of 17.63 mmol g –1 h –1 . This work presents a collaborative strategy for engineering charge behavior in photocatalysts with polarization features, and provides insights into materials design toward photocatalytic hydrogen production and organic synthesis from the angle of charge kinetics. Abstract : The polarization‐induced internal electric field of ZnIn2 S4 material is explored for the first time by engineering the polarity intensity. The integrated design of cascade electric fields in Ni12 P5 /ZnIn2 S4 ‐O polarization photocatalyst with hole transfer vehicle, overcoming the limitations of sluggish charge kinetics and slow hole transfer, achieves highly efficient photocatalytic hydrogen evolution.